PENGEMBANGAN MEDIA PEMBELAJARAN TEMATIK TERPADU BERBASIS MACROMEDIA FLASH 8 DI KELAS IV SD - Yolanda, Yola; Sri Lena, Mai (STKIP Subang, 2021)
This research intends to develop an integrated thematic learning media based on Macromedia Flash 8 in grade IV SD Negeri 02 Tanjuang Puan Abai which is valid, practical and effective. And apply ADDIE type. Subjects were fourth grade teachers at SDN 02 Tanjuang Puan Abai and 21 fourth grade students at SD Negeri 02 Tanjuang Puan Abai. The research revealed: (1) integrated thematic learning media based on Macromedia Flash 8 in grade IV SD which was validated by experts was declared